Volumetric Stability of Lipid Bilayers - Hallinen, Kelsey M. (2012)
In agreement with recent reports, a commercial densimeter has yielded a gradual decrease in lipid molecular volume of DPPC multilamellar vesicle dispersions in the gel phase upon repeated thermal cycling between 10ºC and 50ºC. The considerable size of this decrease would have significant implications for the physical chemistry of biomembranes. In contrast, neutral buoyancy measurements performed with similar thermal cycling indicate no gradual change in lipid volume in the gel phase at 20ºC. Remixing the lipid in the densimeter shows that the apparent volume decrease is an artifact. We conclude that gel phase DPPC bilayers exist in a volumetrically stable phase.